2020
DOI: 10.1186/s12860-020-00284-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of miRNA-146b-5p during myogenic proliferation and differentiation in chicken myoblasts

Abstract: Background: In the poultry and livestock industries, precise genetic information is crucial for improving economic traits. Thus, functional genomic studies help to generate faster, healthier, and more efficient animal production. Chicken myoblast cells, which are required for muscle development and regeneration, are particularly important because chicken growth is closely related to muscle mass. Results: In this study, we induced expression of microRNA-146b-5p mediated by the piggyBac transposon system in prim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…MiRNAs which are negative in proliferation usually display a positive role in myoblast differentiation. 34 MiR-743a-5p actually enhanced differentiation and promoted myotubes formation. It displayed a potential positive role in differentiation.…”
Section: Discussionmentioning
confidence: 90%
“…MiRNAs which are negative in proliferation usually display a positive role in myoblast differentiation. 34 MiR-743a-5p actually enhanced differentiation and promoted myotubes formation. It displayed a potential positive role in differentiation.…”
Section: Discussionmentioning
confidence: 90%
“…We noticed that many miRNAs involved in cell proliferation and migration have been identified, such as miR-20b-5p, which was proved to participate in the epithelial mesenchymal transition (EMT), migration and invasion process of prostate cancer [ 45 ]. MiR-146b-5p played a regulatory role in the proliferation and differentiation of human fibroblasts and chicken myoblasts [ 46 , 47 ]. MiR-21-5p is up-regulated in a variety of cancer cells such as non-small cell lung cancer, Hepatocellular carcinoma, melanoma, and colon adenocarcinoma cells, and has been shown to promote cell proliferation [ 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the embryonic period, myoblasts grow and transform into different types of muscle fibers, which determine the number of muscle fibers after birth [ 57 ]. Many studies have shown that miRNAs affect the growth and differentiation of myoblasts in vitro.…”
Section: Mirna Modulates Skeletal Muscle In Domestic Chickenmentioning
confidence: 99%